Qualitative Research on the Impact of Information and Communication Technology on Penang Port Sdn. Bhd - Arbak, Salwani; Yaakub, Sabariah; Wan Mohamad Zakari, Wan Hanisah (AiBMA Management, 2017)
The use of (ICT) in logistics has been advocated to enhance the performance of the logistics sector especially in the seaports. A huge number of researches showed the importance of using RBV in analyzing performance. RBV however has been adopted in accordance to address the implication of IT on performance for many years, and the latest findings on “IT-performance” relationship is very unclear to make a conclusion. Therefore, further study on application of this theory in the ICT-performance relationship in port industry. This study seeks to examine the impact of ICT implementation on Penang Port Sdn. Bhd. (PPSB) performance. This research is exploratory in nature and the data was collected through a series of interviews. The result from this study shows that there are impact on the ICT usage, container management and Smart-Rail system on port performance. However, this study indicates that port security system does not give an impact towards achieving overall port performance. This study found that technology resources raise internal and external capabilities, which in turn affect port performance. Port resources positively affect organizational efficiency through its impact on internal capabilities thus directly impact the port performance. The results of this study provide direction for investing and managing organizational it resources to achieve competiveness.